2011
DOI: 10.1002/hbm.21241
|View full text |Cite
|
Sign up to set email alerts
|

The influence of emotional associations on the neural correlates of semantic priming

Abstract: Emotions influence our everyday life in several ways. With the present study, we wanted to examine the impact of emotional information on neural correlates of semantic priming, a well-established technique to investigate semantic processing. Stimuli were presented with a short SOA of 200 ms as subjects performed a lexical decision task during fMRI measurement. Seven experimental conditions were compared: positive/negative/neutral related, positive/negative/neutral unrelated, nonwords (all words were nouns). Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 130 publications
(178 reference statements)
11
26
0
Order By: Relevance
“…Activation in response to valenced words, collapsing across concreteness, in this analysis included bilateral temporal pole, STS, and angular gyrus, left IFG, and portions of the anterior and posterior cingulate cortex. These findings, particularly the medial activations, are highly consistent with other neuroimaging studies of single word reading of emotional words (Kuchinke, Jacobs, Grubich, Vo, Conrad & Herrmann, 2005; Nakic, Smith, Busis, Vythilingam, & Blair, 2006; Sass, Habel, Sachs, Huber, Gauggel & Kircher, 2012). …”
Section: Discussionsupporting
confidence: 90%
“…Activation in response to valenced words, collapsing across concreteness, in this analysis included bilateral temporal pole, STS, and angular gyrus, left IFG, and portions of the anterior and posterior cingulate cortex. These findings, particularly the medial activations, are highly consistent with other neuroimaging studies of single word reading of emotional words (Kuchinke, Jacobs, Grubich, Vo, Conrad & Herrmann, 2005; Nakic, Smith, Busis, Vythilingam, & Blair, 2006; Sass, Habel, Sachs, Huber, Gauggel & Kircher, 2012). …”
Section: Discussionsupporting
confidence: 90%
“…This finding supports a large body of research suggesting that healthy individuals generally exhibit a positivity bias, which affects many aspects of cognition, e.g., [28,29]. For example, during studies on automatic semantic processing it was shown that subjects process positive information easily and comparable to neutral information while negative information is suppressed or even inhibited, e.g., [10]. In addition, as the task is not only based on emotional processing but also on cognitive processes, the presentation of a emotionally negative word might “interfere” with the cognitive processes leading to inferior performance (see also [10] for a discussion of emotional interference with cognitive processes).…”
Section: Discussionsupporting
confidence: 81%
“…In this kind of model, mOFC would be involved in overseeing the scope of associative processing such that positively valenced signals would trigger a broadening of this scope, and signals indicating negative valence in an object would result in narrowing this scope through inhibition of associative processing by mOFC (cf. Sass, et al, 2011), similarly to what is seen in the narrowing of attentional focus for negatively valenced stimuli (Baddeley, 1972; Gasper & Clore, 2002). While still largely hypothetical, this model gains support from recent findings in rhesus macaques showing that nearby perigenual ACC (BA 32) projects to regions of parahippocampal cortex in ways that would allow it to exert excitatory and inhibitory control over the local information processing circuitry (Bunce & Barbas, 2011).…”
Section: Discussionsupporting
confidence: 65%
“…Directly replicating previous studies of associativity (Aminoff, Schacter, & Bar, 2008; Bar & Aminoff, 2003), we found that neutral objects with strong associations significantly increased BOLD activity in mOFC, when compared to weakly associative objects (left: F (1,54) = 33.3; right: F (1,54) = 15.4; p ’s<0.001, corrected). Mirroring findings for a number of different kinds of affectively valenced stimuli (Brown, et al, 2011; Chib, Rangel, Shimojo, & O’Doherty, 2009; Lebreton, Jorge, Michel, Thirion, & Pessiglione, 2009; Nielen, et al, 2009; O’Doherty, Critchley, Deichmann, & Dolan, 2003a; Sass, et al, 2011), BOLD activity in mOFC also increased significantly for Positive objects compared with the neutrally valenced objects (i.e., Neutral-Strong and Neutral-Weak combined) and compared with the Negative objects (left: F (3,72) = 8.2, p <0.001, corrected; right: F (3,72) = 3.4, p <0.05, corrected; Fig. 2c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation